Projetos de memória e imagem institucional: um estudo de caso do Banco Itaú - Bezamat, Manuela Cavalcante (2013)
A phenomenon that has suffered a major growth in the last few decades, the constitution of corporate memory projects takes place in a broader context of valorization of the past in the modern day society, characterized by the ‘memory fever’. A p art of a n expedient that has the final goal of strengthen ing the identity and the image of these institutions among their employees and the larger public, these init iatives have generated different products and lines of action , being initially connected to the marketing and communication fields, but showing signs of professionalization and broadening of their horizons. The present study had as an object Banco Itaú’s corporate memory project, created in 2003, aiming to understand the nature of this initiative and the representations of ‘’archive’’, ‘’ legacy’’ and ‘’tradition’’ that were used. Furthermore , it was sought to analyse how this project reinforces and updates the bank’s ‘’cultural calling’’, legitimizing, through its archive and a series of actions, the corporate speech regarding the investme nt in the arts, science and culture.